2020
DOI: 10.1097/j.jcrs.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Propensity and quantification of aerosol and droplet creation during phacoemulsification with high-speed shadowgraphy amid COVID-19 pandemic

Abstract: Purpose: To study propensity of aerosol and droplet generation during phacoemulsification using high-speed shadowgraphy and quantify its spread amid COVID-19 pandemic. Setting: Aerosol and droplet quantification laboratory. Design: Laboratory study. Methods: In an experimental set-up, phacoemulsification was performed on enucleated goat eyes and cadaveric human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…But this study did not include particles of size less than 20 microns and invisible aerosols into consideration. [ 4 ] It is understood that even high-resolution cameras can detect only particles of size more than 10 microns. [ 3 ] But, the SARS-CoV-2 aerosols were mainly found to include two size ranges, one in the sub-micrometer region (dp between 0.25 and 1.0 µm) and the other in super micrometer region (dp >2.5 µm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But this study did not include particles of size less than 20 microns and invisible aerosols into consideration. [ 4 ] It is understood that even high-resolution cameras can detect only particles of size more than 10 microns. [ 3 ] But, the SARS-CoV-2 aerosols were mainly found to include two size ranges, one in the sub-micrometer region (dp between 0.25 and 1.0 µm) and the other in super micrometer region (dp >2.5 µm).…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 ] Some studies have demonstrated aerosol formation, while other studies provide contradictory data. [ 4 ] The latter have not commented about the visualisation of particles of size less than 20 microns.…”
mentioning
confidence: 99%
“…Surgical staff wore appropriate personal protective equipment. Techniques shown to reduce aerosolisation were utilised where possible during phacoemulsification: use of 2.2-mm phaco tip [1], hydroxypropyl methylcellulose application on corneal incision [1], tip placement away from corneal incision [4], in addition to routine use of povidoneiodine for cleaning and complete viscoelastic exchange of anterior chamber fluid before capsulorrhexis. Theatre floors were disinfected between cases and all surgery performed under local anaesthesia.…”
Section: To the Editormentioning
confidence: 99%
“…9 Other groups have also demonstrated similar findings in porcine eyes and goat eyes mounted with human cadaveric corneoscleral rim. [10][11][12] However, these studies were all conducted in a simulated setting, while confirmatory studies of phacoemulsification in real-world settings have yet to be conducted. The living human cornea biomechanics also differs from plastic model eyes and cadaveric eyes.…”
Section: Introductionmentioning
confidence: 99%